Patrones y procesos de invasión de plantas en los alrededores del Macizo de Iguaque (Boyacá, Colombia) (2020)
Biological invasions are one of the greatest threats facing natural and semi-natural ecosystems, they generate great negative impacts that affect the ecosystems, being the second cause of species extinction in the world. The invasion process is highly complex and responds to many factors that change according to the context of the place. It is recognized that the main variables involved are related to climatic conditions, land uses, features of the life history of the species and the invasion credit accumulated by the history of the place. Taking into account that the study of invasion patterns (distribution, richness and abundance) and the variables involved are fundamental to understanding the processes and mechanisms of invasion and prevention and control strategies, the present work in ecosystems was developed. Alto Ricaurte (Boyacá, Colombia) which have been subject to a wide variety of pressures of different nature, generating ideal scenarios for the establishment and expansion of exotic species with characteristics of invaders. The four most representative transformation scenarios of the region were sampled: roads, urban centers, bodies of water and the surroundings of the Iguaque Massif. Initially, a list of 40 invasive plant species was generated, 26 of these were selected for intensive sampling of their spatial distribution, individuals and patches were georeferenced and the most persistent life history traits of the species and invasion hot spots were determined. Subsequently, with the implementation of GIS tools in the software QGIS, the behavior of the richness, abundance and size of patches in each of the four scenarios and the main ecological processes associated with the invasion patterns were determined. This work is expected to be a contribution to the knowledge of biological invasions in Colombia, in addition to providing tools for the planning of new studies and the development of prevention and control strategies.